Design and analysis front hood fairing for cars - Mahasufee, Mahazis (2009)
This report is an outcome of the work carried out in doing and completing my final year project, Design and analysis front hood fairing for cars. The paper presents a model of the front hood fairing for cars that can reduce the drag coefficient of the car, model that been used is proton Iswara. The overall duty is modeling and analyzes to get the best model that can reduce the coefficient of drag of the proton Iswara because of the high drag force at front windscreen. It happen when the airflow at the windscreen is disturbed by car wiper during high speed. It is often that the wiper system generates unwanted noise and vibration during the high speed. The report starts off with an introduction in aerodynamics vehicle and design. Then proceed to investigation about the problem at the front windscreen to get information. After gathering all the relevant information, the project undergoes design process. In this steps, from the knowledge gathered before is use to make a design refers to case data that suitable for the project. Several sketches have been made and only a few have been selected based on the suitability of the front hood and dimension of the windscreen. Based on the sketches, all the sketches will be draw into CAD software and simulate in the CFD software. At the end, the fairing that can reduce more coefficient of drag will be selected. The result shown by adding fairing at the front hood will decrease the pressure and wind noise also can be reduced. Then, the airflow will smooth and the performance of the car greater than before.